How does transtrochanteric anterior rotational osteotomy change the dynamic three-dimensional intact ratio in hips with osteonecrosis of the femoral head?. (February 2021) - Hara, Daisuke; Hamai, Satoshi; Miller, Kyle R.; Motomura, Goro; Yoshimoto, Kensei; Komiyama, Keisuke; Shiomoto, Kyohei; Ikemura, Satoshi; Nakashima, Yasuharu; Banks, Scott A.
Abstract: Background: The intact ratio (the ratio of the intact area of the femoral head) on a two-dimensional anteroposterior radiograph is associated with the prognosis of hips with osteonecrosis of the femoral head after transtrochanteric anterior rotational osteotomy. However, changes of the three-dimensional intact ratio during dynamic weight-bearing activity and correlation of the three-dimensional intact ratio with clinical scores are still unknown. Methods: Kinematics of eight hips with osteonecrosis of the femoral head that underwent anterior rotational osteotomy were analyzed using image-matching techniques during chair-rising and squatting preoperatively and postoperatively. Two types of dynamic three-dimensional intact ratios were examined, including the lunate covered area (IRLC ) and in vivo peak contact force vector intersected area (IRFV ). The static three-dimensional intact ratio in each octant of the femoral head was also examined. Findings: The mean Harris hip score significantly improved from 67 preoperatively to 90 postoperatively. During chair-rising rising/squatting, the mean IRLC and IRFV significantly increased from 42%/41% and 7%/4% preoperatively, to 66%/65% and 79%/77% postoperatively, respectively. IRLC significantly changed during the motion whereas substantial postoperative IRFV was maintained throughout the motion. Additionally, Harris hip score and the static three-dimensional intact ratio in the superolateral regions had significant positive correlations with both IRLC and IRFV . Interpretation: Hip kinematics affected IRLC but not IRFV, which suggests that substantial intact bone occupies the region in which peak contact forces are applied during deep hip flexion. Additionally, improving intact ratio in the superolateral region led to improvements in both IRLC and IRFV with favorable clinical scores. Highlights: In-vivo 3D kinematics of hips with osteonecrosis of the femoral head were examined. 3D dynamic intact ratios pre and post femoral osteotomy were quantified. Lunate covered 3D intact ratio significantly changed during the hip flexed motions. Operated hips showed enough 3D intact ratio in the peak contact force applied area. 3D intact ratio in statics at specific regions was associated with that in dynamics.